Giovanni Battista Kanano (1515-1579) - Kutya, S. A.; Nazarevskaya, M. P.; Pikalyuk, V. S.; Moroz, G. A.; Kriventsov, M. A. (Морфологія / Morphologia / Morfologìâ, 2015)
In the 16th century, the Ferrara anatomical school was in the shadow of other Italian schools and, above all, of the Padua school. Despite this, it is necessary to mention the names Gabriela Fallopio, who started his way to the anatomical heights in Ferrara, and Giovanni Battista Canano, whose 500th birthday is celebrated this year.